Efektivitas Media Edukasi Terhadap Perilaku Bersih Dan Sehat Dalam Komunitas : Literatur Review - Mellia Anata Tasya; Rahma Amalia; Sevia Diva Ardiansyah; Vanessa Priscila Takwin; Isnaini .; Nabila .; Nursela .; Nur Azzahra Atikah; Tri Wahyu Sapitri Syam; Nurhidayah .; Dwi Widyastuti (Jurnal Sains Farmasi Dan Kesehatan, 2026)
Clean and Healthy Living Behavior (PHBS) is a key strategy in public health promotion aimed at improving quality of life through behavioral change. According to data from the Indonesian Ministry of Health, the implementation of PHBS has not yet been fully integrated into daily life, highlighting the need for effective educational approaches. This study aims to examine the effectiveness of various educational media on PHBS behavior in communities through a systematic literature review. Articles were collected from the Garuda and Google Scholar databases, covering publications from 2021 to 2025. The selection process followed PRISMA guidelines and resulted in eight articles that were analyzed based on study design, type of educational media, and intervention outcomes. The findings indicate that educational media such as videos, social media, posters, leaflets, educational games, lectures, and discussions contribute to improving knowledge, attitudes, and PHBS practices. Social media and videos demonstrate strong potential for broad and repeated information dissemination, while print media and direct methods are more suitable for populations less familiar with technology. These findings suggest that educational media are an effective and relevant approach to enhancing PHBS implementation in the community.